65.5k views
5 votes
Need help with this question?

Need help with this question?-example-1

1 Answer

2 votes

Answer:

The equation is
x^(2) +2\cdot x + 2 = 0-

Explanation:

According to the statement, we have a second order polynomial of the form
A\cdot x^(2)+ B\cdot x + C = 0, whose solutions can be found by Quadratic Formula:


x_(1,2) = \frac{-B\pm \sqrt{B^(2)-4\cdot A\cdot C}}{2\cdot A} (1)

Where
A,
B and
C are the coefficients of the polynomial.

If roots are conjugated complex numbers, then:


B^(2)-4\cdot A\cdot C < 0 (2)


B^(2) < 4\cdot A \cdot C

If we know that
A = 1,
C = 2 and
x_(1,2) = -1\pm i, then we find that:


-1\pm i = -(B)/(2)\pm \frac{\sqrt{B^(2)-8}}{2}


-2 \pm i\,2 = -B \pm \sqrt{B^(2)-8}

By comparing each side, we have the following system of equations:


-B = -2 (3)


\sqrt{B^(2)-8} = 2 (4)

Whose solution is
B = 2.

In a nutshell, the equation is
x^(2) +2\cdot x + 2 = 0-

User Eyni Kave
by
4.6k points